Functions of MDA5 and its domains in response to GCRV or bacterial PAMPs. Issue 2 (October 2015) - Gu, Tianle; Rao, Youliang; Su, Jianguo; Yang, Chunrong; Chen, Xiaohui; Chen, Lijun; Yan, Nana
Abstract Melanoma differentiation-associated gene 5 (MDA5) is a member of retinoic acid-inducible gene I (RIG-I)-like receptor (RLR) family which can initiate type I IFN expression in response to RNA virus infection. In this study, we constructed six mutants of Ctenopharyngodon idella MDA5 (CiMAD5) overexpression plasmids and generated stable transfected C. idella kidney (CIK) cell lines to study the function of different domains of CiMAD5. After ploy(I:C) stimulation, the downstream genes of CiMDA5 in transfected cells was repressed. Overexpression of CiMDA5 or its variant repressed the replication of grass carp reovirus (GCRV) in CIK cells and decreased the viral titer of GCRV more or less compared to that in control cells. After GCRV or bacterial pathogen-associated molecular patterns (PAMPs) stimulation, overexpression of CiMDA5 or CARD domain significantly induced the expression of CiIFN-I, CiIL-1β and CiMx1. The deletion of Helicase or RD domain reduced the inductive effect of CiMDA5 on CiIFN-I, CiIL-1β and CiMx1 expression. RD overexpression resulted in an enhanced expression of CiIFN-I, CiIL-1β and CiMx1. These observations collectively demonstrate that, in CIK cells, after GCRV or bacterial PAMPs stimulation, CARD domain alone can mediate signaling; Helicase or RD domain alone negatively regulates CARD function by intramolecular interaction with CARD. However, RD domain acts as an enhancer by intermolecular interaction. These results enlarge the response spectrum of MDA5 and contribute to a further understanding of the functions of MDA5 and its domains in evolution.